Determinant Effective Tax Rate Thru Return On Asset, Managerial and Institutional Ownership - Gita Fatwa Qurniati; Wajib Ginting; Kartika Berliani (Komunitas Dosen Indonesia, 2026)
This study examines the effects of the return on assets, managerial ownership and institutional ownership on Effective Tax Rate of Indonesian Properties and Real Estate industry between 2017 and 2024. Employing a quantitative approach that adopts a descriptive and verificative strategy, the study looks at 93 financial statements from specific Properties dan Real Estate industry. The correlations between the variables were evaluated using analysis of multiple regression analysis, the coefficient of determination examination, traditional assumption tests, as well as the correlation coefficient test for product moments such as t-tests and F-tests for assessing hypotheses. The incomplete test results show that ROA has a positive effect on ETR, but institutional and management ownership have no effect. However, the results of the simultaneous test indicate that when combined, ROA, management ownership, and institutional ownership have a significant impact on ETR. These findings indicate that in the properties and real estate sector, activity ROA, management ownership, and institutional ownership mix are more significant determinants of Effective Tax Rate than short-term.